In Vitro Plant Regeneration from Cultured Cotyledons of Cotton (Gossypium herbaceum L.) - Chowdhury, AN; Rahman, MZ; Samad, A; Alam, AKMS; Khaleda, S (Bangladesh Journal of Scientific and Industrial Research, 2011)
The effect of cytokinins on callus proliferation from cotyledons and plantlet development was studied in cotton. The frequency of callus induction was observed on MS medium enriched with a variety of cytokinins in different concentrations. With the increase of cytokinin concentration, the percentage of callus formation, percentage of shoot developing calli and number of shoots/calli were increased. Among the three different cytokinins studied, BA showed the highest performance. The highest percentage of callus (6.55%) and shoot developing calli (5.87%) was obtained on MS with 1.0 mg/l BA. Highest number of shoots (3.02) per calli was observed on MS media supplemented with 1.0 mg/l Kn. The rooting media composed of MS medium, 0.6% agar, sucrose and fortified with 2.0 mg/l NAA induced root development at the highest percentage (41.23%) with maximum number of roots (3.61) per cutting and length of root (3.62 cm) per culture. The plantlets were acclimatized in natural conditions. Key words: In vitro; Callus; Cotyledons; Cytokinin; Plantlet; Acclimatization DOI: http://dx.doi.org/10.3329/bjsir.v46i3.9043 BJSIR 2011; 46(3): 359-364